69. Abdominal acupuncture reduces pain at the spinal cord level. Issue 12 (December 2017) - Valeriani, M.; Liguori, S.; Coraci, D.; Pecchioli, C.; Liguori, A.; Padua, L.; Pazzaglia, C.
Abstract : Abdominal acupuncture (AA) reduces laser-evoked potentials (LEP) amplitude and laser pain perception in healthy subjects (Pazzaglia et al., 2014). The aim of the current study was to investigate the site of AA analgesic effect. We recorded LEPs in 10 healthy volunteers by using the 32 EEG scalp electrodes. The experimental protocol included 3 times: (1) baseline, in which LEPs to stimulation of the bilateral dorsal wrist and right foot were recorded before acupuncture; (2) acupuncture, in which LEPs were recorded during AA performed in the abdominal area corresponding to right wrist; and (3) rest, in which LEPs were recorded 15 min after the needle removal. The N2/P2 LEP amplitude to stimulation of both wrist was reduced in the acupuncture and rest times as compared to baseline, while LEP amplitude to foot stimulation was not modified. Abdominal acupuncture is able to reduce LEP amplitude. Since the homotopic regions of both sides are possibly connected within the spinal cord, our results suggest that the AA analgesic effect occurs at spinal level. On the other hand, the absence of any modulation of LEPs to foot stimulation is against the possibility of an AA general inhibitory effect.